Penerapan Metode Profile Matching pada Sistem Penyusunan Formasi Sukarelawan Event Organizer (Studi Kasus: XYZ Event Organizer) - Sirait, Tamsir Hasudungan; Gunawan, Kevin T. (Yayasan Petra Harapan Bangsa, 2020)
XYZ Event Organizer is an international event organizer that is engaged in serving choir events. Its vision is to build a strong choir life in Indonesia by organizing many events such as concerts, seminars, choral music workshops, collaborations, choir clinics, competitions, and symposiums. In holding an event, a committee structure is needed which will be determined by the project manager. In the preparation of this human resource formation, there were obstacles caused by data that was not integrated into the formation process, nor can companies provide direct line-ups from their scoring system without going through a repeated interview process. With a system that is designed online and with a system that is integrated in one database, data that is not integrated, redundancy, and inconsistencies can be handled so that it does not require additional time and effort in dealing with these problems. By using the profile matching method each volunteer can be seen the assessment of each division of the required criteria. By using an algorithm in accordance with the rules given by the company, namely the calculation of answer points in the system, and by following the rules for the profile matching method, an allocation of volunteer formation arrangements is obtained. The allocation is taken from the volunteer proximity value with the standard value given by the company. XYZ Event Organizer merupakan event organizer internasional yang bergerak dalam melayani event paduan suara. Visinya membangun kehidupan paduan suara yang kuat di Indonesia. Dengan menyelenggarakan banyak acara seperti konser, seminar, lokakarya musik paduan suara, kolaborasi, klinik paduan suara, kompetisi dan simposium. Dalam mengadakan event, pertama-tama dibutuhkan susunan panitia yang akan ditentukan oleh project manager. Pada penyusunan formasi sumber daya manusia ini terjadi hambatan yang disebabkan adanya data yang tidak terintegrasi dalam melakukan proses penyusunan formasi. Perusahaan pun tidak dapat memberikan susunan formasi secara langsung dari sistem penilaiannya tanpa melalui proses wawancara berulang. Dengan sistem yang dirancang secara online dan dengan sistem yang diintegrasikan dalam satu database, maka data yang tidak terintegrasi, redundansi, dan inkonsistensidapat ditangani sehingga tidak memerlukan waktu dan tenaga tambahan dalam menangani masalah tersebut. Dengan menggunakan metode profile matching setiap sukarelawan dapat terlihat penilaian setiap divisi dari kriteria-kriteria yang dibutuhkan. Dengan menggunakan algoritma yang sesuai dengan aturan yang diberikan oleh perusahaan, yaitu perhitungan poin jawaban di dalam sistem, dan dengan mengikuti aturan metode profile matching, maka didapatlah sebuah alokasi susunan formasi sukarelawan. Alokasi tersebut diambil dari nilai kedekatan sukarelawan dengan nilai standar yang diberikan oleh perusahaan.